2007
DOI: 10.1007/s11695-007-9185-0
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the use of the Beck Depression Inventory in the Assessment of Weight-Loss Surgery Seeking Patients

Abstract: The factor structure of the BDI in this population is similar to that in other non weight-loss surgery populations. However, this population is more likely to endorse somatic complaints that may not be indicative of depression, rather an acknowledgement of actual medical complaints. Thus, assessors should be mindful of specific symptom endorsement, rather than a total depression score when utilizing the BDI to help determine surgery suitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 16 publications
5
39
0
Order By: Relevance
“…The data simulation was performed using R software 2.6.2.; vectors ε j , f m and C were generated using the function rnorm and δ j using runif. (Bell et al, 1994;Fresan et al, 2005;Honey et al, 2003;Kay et al, 1990;Lancon et al, 1999;Lee et al, 2003;Lindenmayer et al, 2004;Loza et al, 2003;Lykouras et al, 2000;Salokangas et al, 2002;Villalta-Gil et al, 2006) 11 --1 8 -2 BPRS (Adachi et al, 2000;Harvey et al, 1996;Lachar et al, 2001;Ventura et al, 2000) 4 --2 1 1 -BAI (Beck, 1991;Chapman et al, 2009;Kabacoff et al, 1997;Steer et al, 1995;Steer et al, 1993) (Gabryelewicz et al, 2004;Galinowski et al, 1995;Lee et al, 2003;Parker et al, 2003;Serretti et al, 1999) 5 3 2 ----BDI (Basker et al, 2007;Bonicatto et al, 1998;Bonilla et al, 2004;Gorenstein et al, 1999;Grunebaum et al, 2005;Helm et al, 2003;Jo et al, 2007;Killgore, 1999;Munoz et al, 2007;Powell, 2003;Salamero et al, 1994;Shek, 1990;Steer et al, 1989;Uslu et al, 2008;Wang et al, 2005) …”
Section: Resultsmentioning
confidence: 99%
“…The data simulation was performed using R software 2.6.2.; vectors ε j , f m and C were generated using the function rnorm and δ j using runif. (Bell et al, 1994;Fresan et al, 2005;Honey et al, 2003;Kay et al, 1990;Lancon et al, 1999;Lee et al, 2003;Lindenmayer et al, 2004;Loza et al, 2003;Lykouras et al, 2000;Salokangas et al, 2002;Villalta-Gil et al, 2006) 11 --1 8 -2 BPRS (Adachi et al, 2000;Harvey et al, 1996;Lachar et al, 2001;Ventura et al, 2000) 4 --2 1 1 -BAI (Beck, 1991;Chapman et al, 2009;Kabacoff et al, 1997;Steer et al, 1995;Steer et al, 1993) (Gabryelewicz et al, 2004;Galinowski et al, 1995;Lee et al, 2003;Parker et al, 2003;Serretti et al, 1999) 5 3 2 ----BDI (Basker et al, 2007;Bonicatto et al, 1998;Bonilla et al, 2004;Gorenstein et al, 1999;Grunebaum et al, 2005;Helm et al, 2003;Jo et al, 2007;Killgore, 1999;Munoz et al, 2007;Powell, 2003;Salamero et al, 1994;Shek, 1990;Steer et al, 1989;Uslu et al, 2008;Wang et al, 2005) …”
Section: Resultsmentioning
confidence: 99%
“…In this study, there was no significant effect on weight loss based on the incidence of depressive symptoms as assessed by the BDI. Munoz et al [19] have suggested that use of a total BDI score may not accurately identify depressed patients as the BDI items fall into either cognitive/affective or somatic factors. The cognitive/affective factors primarily reflect depressive thoughts and feelings, whereas the somatic items represent health and wellness concerns and physical incapacity.…”
Section: Discussionmentioning
confidence: 99%
“…Munoz and colleagues [10] recently investigated the use of the BDI in a bariatric surgery population. They compared endorsements of the cognitive-affective items on the BDI to the somatic items in a bariatric surgery population.…”
mentioning
confidence: 99%